2021
DOI: 10.1098/rspb.2021.0454
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to artificial light at night in the wild decreases survival and growth of a coral reef fish

Abstract: Artificial light at night (ALAN) is an increasing anthropogenic pollutant, closely associated with human population density, and now well recognized in both terrestrial and aquatic environments. However, we have a relatively poor understanding of the effects of ALAN in the marine realm. Here, we carried out a field experiment in the coral reef lagoon of Moorea, French Polynesia, to investigate the effects of long-term exposure (18–23 months) to chronic light pollution at night on the survival and growth of wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 75 publications
3
20
2
Order By: Relevance
“…Over a period of about 8–11 weeks, offspring from high‐flow parents had higher mortality and slower growth compared to those from low‐flow parents, regardless of the flow conditions they settled into. Despite the majority of mortality occurring at settlement (~82% within 4 days after settlement), the overall mortality rate was comparable with another laboratory‐reared field‐based experiment on A. chrysopterus , which showed 50% survival on early life stages (Schligler et al, 2021). Adult fish may invest less into reproductive output to maximise their own growth and survival during unfavourable or more demanding environmental conditions (Green, 2008; Reznick et al, 2000).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Over a period of about 8–11 weeks, offspring from high‐flow parents had higher mortality and slower growth compared to those from low‐flow parents, regardless of the flow conditions they settled into. Despite the majority of mortality occurring at settlement (~82% within 4 days after settlement), the overall mortality rate was comparable with another laboratory‐reared field‐based experiment on A. chrysopterus , which showed 50% survival on early life stages (Schligler et al, 2021). Adult fish may invest less into reproductive output to maximise their own growth and survival during unfavourable or more demanding environmental conditions (Green, 2008; Reznick et al, 2000).…”
Section: Discussionsupporting
confidence: 72%
“…Our study also raises other questions, such as morphological and physiological plasticity across male and female stages or the survival and dispersal implications of different larval fish morphotypes. (~82% within 4 days after settlement), the overall mortality rate was comparable with another laboratory-reared field-based experiment on A. chrysopterus, which showed 50% survival on early life stages (Schligler et al, 2021). Adult fish may invest less into reproductive output to maximise their own growth and survival during unfavourable or more demanding environmental conditions (Green, 2008;Reznick et al, 2000).…”
Section: Discussionsupporting
confidence: 69%
“…It is therefore unclear whether ALAN in more natural settings, and over longer periods of time, will lead to similar alterations to hormone levels. However, one recent study in a natural setting showed that longterm exposure to light pollution over 18-23 months negatively impacts the survival and growth of a wild coral reef fish (Schligler et al, 2021). The higher mortality of orange-fin anemonefish, A. chrysopterus, in the wild (Schligler et al, 2021) agrees with a laboratory study showing increased predation under ALAN of coral reef fish larvae, the convict tang, Acanthurus riostegus (O'Connor et al, 2019).…”
Section: Artificial Light Pollution At Nightsupporting
confidence: 57%
“…In most cases, all the above experiments on ALAN were completed in laboratory settings lacking many environmental and ecological factors, such as species interactions between predators and prey, as well as refuges linked to habitat complexity (Brüning et al, 2015;Schligler et al, 2021). It is therefore unclear whether ALAN in more natural settings, and over longer periods of time, will lead to similar alterations to hormone levels.…”
Section: Artificial Light Pollution At Nightmentioning
confidence: 99%
“…The use of VR offers countless new research opportunities including to better understand behaviours of coral reef fish in response to local and global changes (5457) and how they impact the role of vision in habitat selection at recruitment. To understand the mechanisms involved in the visual recognition of conspecifics or predators, our VR set-up can be used to manipulate as many visual factors as needed, including size, colour patterns, fin arrangements, but also the behaviour of other individuals (aggressive, curious, social, fleeing).…”
Section: Discussionmentioning
confidence: 99%